Seasonal fluctuations of noctuid stemborer egg parasitism in southern Benin with special reference to Sesamia calamistis Hampson (Lepidoptera:Noctuidae) and Telenomus spp (Hymenoptera:Scelionidae) on maize - Schulthess, F.; Chabi-Olaye, A.; Goergen, Georg E. (Informa UK Limited, 2001)
Parasitism of noctuid stemborer eggs was assessed in monthly surveys in maize fields in southern Benin, from May 1995 to October 1996, and on alternative hosts, i.e. wild grasses, during the dry season from November 1995 to February 1996. Sesamia calamistis was the most prevalent stemborer species, accounting for 98% of the larvae identified from subsamples reared on ear pieces. Egg batch densities ranged between 0.02-0.15 per plant, with lowest densities found during high rainfall periods. 77% of all egg batches were found to be parasitized The egg parasitoids were the scelionids Telenomus busseolae, T. isis , and the trichogrammatid Lathromeris ovicida , accounting for 55.6, 41.6 and 2.8% of total counts, respectively. Parasitism increased in the course of the cropping season and reached peaks of 92 and 86% during the second growing season of 1995 and 1996, respectively. This coincides with the time when farmers have planted a second crop and during a stage when the plants were most attractive and susceptible to S. calamistis attacks. During the dry season, relatively high parasitism was found on maize and wild grasses in inland valleys, and it was concluded that those habitats play an important role in stabilizing the system for both the pest and its natural enemies. As a result, in the Dahomey Gap, which includes parts of Benin, Togo and Ghana, S. calamistis is usually not of economic importance. Although T. busseolae is ubiquitous in Africa, T. isis was only reported from West Africa, including Cameroon. It is recommended that the geographic range of T. isis should be expanded and include East and Southern Africa, where another host, Busseola fusca , is the most important noctuid stemborer pest on cereals.